Selection of the bovine papillomavirus type 1 nucleotide 3225 3' splice site is regulated through an exonic splicing enhancer and its juxtaposed exonic splicing suppressor. - Zheng, Z M (1996)
Alternative splicing is an important mechanism for the regulation of bovine papillomavirus type 1 (BPV-1) gene expression during the virus life cycle. However, one 3' splice site, located at nucleotide (nt) 3225, is used for the processing of most BPV-1 pre-mRNAs in BPV-1-transformed C127 cells and at early to intermediate times in productively infected warts. At late stages of the viral life cycle, an alternative 3' splice site at nt 3605 is used for the processing of the late pre-mRNA. In this study, we used in vitro splicing in HeLa cell nuclear extracts to identify cis elements which regulate BPV-1 3' splice site selection. Two purine-rich exonic splicing enhancers were identified downstream of nt 3225. These sequences, designated SE1 (nt 3256 to 3305) and SE2 (nt 3477 to 3526), were shown to strongly stimulate the splicing of a chimeric Drosophila doublesex pre-mRNA, which contains a weak 3' splice site. A BPV-1 late pre-mRNA containing the nt 3225 3' splice site but lacking both SE1 and SE2 was spliced poorly, indicating that this 3' splice site is inherently weak. Analysis of the 3' splice site suggested that this feature is due to both a nonconsensus branch point sequence and a suboptimal polypyrimidine tract. Addition of SE1 to the late pre-mRNA dramatically stimulated splicing, indicating that SE1 also functions as an exonic splicing enhancer in its normal context. However, a late pre-mRNA containing both SE1 and SE2 as well as the sequence in between was spliced inefficiently. Further mapping studies demonstrated that a 48-nt pyrimidine-rich region immediately downstream of SE1 was responsible for this suppression of splicing. Thus, these data suggest that selection of the BPV-1 nt 3225 3' splice site is regulated by both positive and negative exonic sequences.